2021
DOI: 10.3390/antiox10020268
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti-Oxidative Effect of Human Adipose- and Amniotic Membrane-Derived Mesenchymal Stem Cell Conditioned Medium on Mouse Preimplantation Embryo Development

Abstract: Oxidative stress is a major cause of damage to the quantity and quality of embryos produced in vitro. Antioxidants are usually supplemented to protect embryos from the suboptimal in vitro culture (IVC) environment. Amniotic membrane-derived mesenchymal stem cells (AMSC) have emerged as a promising regenerative therapy, and their paracrine factors with anti-oxidative effects are present in AMSC conditioned medium (CM). We examined the anti-oxidative potential of human AMSC-CM treatment during IVC on mouse preim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…84,85 Therefore, antioxidants are critical compounds in the wound healing and tissue regeneration processes, with antioxidant treatments previously demonstrating the capacity to improve the wound healing process. [84][85][86] Stem cells are known to secrete antioxidants, 87 though upon becoming senescent stem cells have demonstrated a shift in the secretion of oxidants relative to antioxidant compounds. In this study, ASC-CM from the 3D system exhibited a significantly higher level of total antioxidant activity relative to 2D (Figure S5).…”
Section: Secretome From 3d Culture Enhances Kc and Fibroblast Activitymentioning
confidence: 99%
“…84,85 Therefore, antioxidants are critical compounds in the wound healing and tissue regeneration processes, with antioxidant treatments previously demonstrating the capacity to improve the wound healing process. [84][85][86] Stem cells are known to secrete antioxidants, 87 though upon becoming senescent stem cells have demonstrated a shift in the secretion of oxidants relative to antioxidant compounds. In this study, ASC-CM from the 3D system exhibited a significantly higher level of total antioxidant activity relative to 2D (Figure S5).…”
Section: Secretome From 3d Culture Enhances Kc and Fibroblast Activitymentioning
confidence: 99%
“…Recent studies have indicated that mesenchymal stem cells possess antioxidant properties against biological events [ 14 ]. Furthermore, a few studies have reported that mesenchymal stem cells are associated with the development of blastocysts in in vitro-produced embryos, suggesting that certain substances secreted from mesenchymal stem cells may play a critical role in the development of blastocysts [ 8 , 15 ]. In principle, stem cells can self-renew and differentiate into a variety of specialized cell types possessing infinite regenerative potential through their trophic properties [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear whether this positive effect can be attributed to these EVs. To date, a few reports have described that mesenchymal stem cells stimulate the development of blastocysts in in vitro-produced embryos, suggesting that a variety of paracrine factors as well as EVs may participate in the development of blastocysts in in vitro-produced embryos [ 8 , 15 ]. In this study, we aimed to examine the development of blastocysts from in vitro-produced embryos to create a new Transwell culture system for in vitro fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is a major cause of damage to the quantity and quality of embryos produced in vitro. A research paper by Ra et al [11] studied the conditioned medium of amniotic membrane-derived mesenchymal stem cells as a novel antioxidant intervention for assisted reproduction.…”
mentioning
confidence: 99%